Metal polyphenol network coated molybdenum-based nano-enzyme with multiple active centers as well as preparation method and application of metal polyphenol network coated molybdenum-based nano-enzyme

By coating the metal polyphenol network on the surface of molybdenum-based nanoenzyme, the problem of insufficient specificity and selectivity of molybdenum-based nanoenzyme in the tumor microenvironment is solved, its circulation stability and photothermal performance are improved, and high-efficiency tumors are achieved Treatment effect.

CN119456032APending Publication Date: 2025-02-18NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588241.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing molybdenum-based nanoenzymes have weak specificity and selectivity in the tumor microenvironment, poor circulation stability, low tumor site accumulation, and the photo-response diagnostic and treatment performance needs to be optimized.

Method used

Design a metal polyphenol network to coat molybdenum-based nanoenzymes with multi-active centers, prepare iron-molybdenum oxide co-doped mesoporous silica nanoenzymes by gradient calcination, and hydrogenation using metal-acid treatment strategy. Finally, Its surface is coated with a tanninic acid-ferrous metal polyphenol network.

Benefits of technology

The circulating stability and specific catalytic capability of molybdenum-based nanoenzymes are improved, and their photothermal performance and ROS amplification effect are enhanced, achieving excellent optical therapeutic performance and chemical kinetic therapeutic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456032A_ABST
    Figure CN119456032A_ABST
Patent Text Reader

Abstract

The invention provides a metal polyphenol network coated molybdenum-based nano-enzyme with multiple active centers as well as a preparation method and application of the metal polyphenol network coated molybdenum-based nano-enzyme, mesoporous silica is used as a carrier, molybdenum acetylacetonate is used as a molybdenum source, ferric chloride is used as an iron source, stirring is performed for 20 hours, gradient calcination is performed for 4 hours, and the nano-enzyme with iron and molybdenum co-doped mesoporous silica is synthesized. The preparation method comprises the following steps: firstly preparing molybdenum-based nano-enzyme, then hydrogenating the molybdenum-based nano-enzyme by adopting a metal-acid treatment strategy to obtain the molybdenum-based nano-enzyme with multiple enzyme-like catalytic activities (catalase-like, oxidase and peroxidase-like) and efficient near-infrared second-region (1064nm) photothermal conversion capability, continuously stirring the molybdenum-based nano-enzyme with tannic acid (TA) and a ferric chloride solution for 30 minutes, coating the surface of the molybdenum-based nano-enzyme with a TA-Fe metal polyphenol network, and carrying out photothermal conversion on the TA-Fe metal polyphenol network. Therefore, the cycling stability and intratumor specific catalysis of the molybdenum-based nano-enzyme are effectively improved. According to the strategies of the steps, the molybdenum-based nano enzyme which has biological safety and cycling stability and can simultaneously realize excellent optical treatment performance and chemical kinetics treatment performance can be developed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nanozyme preparation, and in particular to a molybdenum-based nanozyme with a metal polyphenol network coating and multiple active centers, a preparation method and an application thereof. Background Art

[0002] In recent years, molybdenum-based nanozymes have become an ideal alternative to traditional enzymes due to their unique multiphase multivalent structure and intrinsic enzyme-like catalytic activity. However, there are still challenging problems in actual treatment. First, the specificity and selectivity of molybdenum-based nanozymes in the highly complex tumor microenvironment (TME) are still weak. Although its enzyme-like activity is diverse, its sustainability and effectiveness need to be improved. Secondly, the accumulation of molybdenum-based nanozymes in tumor sites is still relatively low, which greatly reduces its material utilization. More importantly, in terms of photoresponsive diagnosis and treatment, the ability of molybdenum-based nanozymes to capture light and the performance of photocatalytic generation of reactive oxygen species (ROS) need to be further optimized and improved. Based on this, the development of molybdenum-based nanozymes with diverse functions, high performance and safety is of great significance for the development of catalytic tumor treatment. In order to achieve the target designed molybdenum-based nanozymes, metal polyphenol networks (MPNs) with TME responsive degradation ability are coated on the surface of molybdenum-based nanozymes, which can effectively improve the cyclic stability and intratumor-specific catalysis of molybdenum-based nanozymes, while introducing defect engineering and co-catalysis strategies into molybdenum-based nanozymes to achieve ROS amplification effect while ensuring its excellent photothermal performance. Therefore, it is of great significance to develop molybdenum-based nanozymes with biosafety and cyclic stability and that can simultaneously achieve excellent phototherapeutic properties and chemodynamic therapeutic properties. Summary of the invention

[0003] The object of the present invention is to provide a metal polyphenol-coated molybdenum-based nanozyme with multiple active centers, a preparation method and an application thereof, so as to solve the aforementioned problems existing in the prior art.

[0004] In order to achieve the above object, the technical solution adopted in the present invention is as follows:

[0005] A method for preparing a metal polyphenol-coated molybdenum-based nanozyme with multiple active centers comprises the following steps:

[0006] S1, using mesoporous silica (MSNs), molybdenum ions and iron ions as raw materials, a gradient calcination method was used to prepare Fe-Mo oxide co-doped MSNs nanozymes with multiple enzyme catalytic activities (catalase-like, oxidase, peroxidase-like);

[0007] S2, then adopting the metal-acid treatment strategy to hydrogenate it, will obtain MSNs loaded with hydrogenated iron molybdenum oxide nanozymes Fe-HMMSNs with efficient near-infrared second region (1064nm) photothermal conversion ability;

[0008] S3, using the metal-polyphenol coordination strategy, coated the tannic acid (TA)-Fe metal polyphenol network on its surface to obtain Fe-HMMSNs@TA-Fe, which effectively improved the cyclic stability and intratumor-specific catalysis of Mo-based nanozymes.

[0009] Preferably, the metal polyphenol network coated with a molybdenum-based nanozyme having multiple active centers described in step S1 is characterized in that the MSNs described in step S1 are first dissolved in distilled water with 0.8 to 1.2 g CTA·Tos, 0.1 to 0.2 g tri(2-hydroxyethyl)amine and 10 to 15 mg 1-butyl-3-methyl-imidazolium trifluoromethanesulfonate, and stirred at 80 to 120° C. for 1 to 3 hours, and then 7 to 11 mL ethyl orthosilicate is added, and stirring is continued for 1 to 3 hours, and then the product is centrifuged and washed, and the product is dispersed in anhydrous ethanol for 20 to 26 hours in order to remove the template CTA·Tos. After centrifugation, it is washed and dried, and the obtained solid is MSNs.

[0010] Preferably, step S1 specifically includes: dissolving 25-45 mg MSNs in anhydrous ethanol, then adding a mixed solution of urea and NH4Cl, stirring for 2-3 hours, adding 0.4-0.5 g acetylacetonate molybdenum oxide dispersed in 20-40 mL anhydrous ethanol, continuing stirring for 5-8 hours, and then adding 60-70 mg FeCl3·6H2O dissolved in 2-5 mL anhydrous ethanol, stirring for 20-24 hours. The obtained product is dried in an oven at 40-60° C., the obtained solid is fully ground in a mortar, and finally gradient calcined in a muffle furnace, the maximum temperature is 400-500° C., and the calcination time is 4-6 hours to obtain Fe-MMSNs.

[0011] Preferably, step S2 specifically comprises: dissolving 0.1-0.15 g of Fe-MMSNs in 20-40 mL of dilute hydrochloric acid, the concentration of which is 3-6 M, and then adding 0.1-0.2 g of zinc powder under rapid stirring conditions to react for 3-8 min to obtain a blue-black product, which is then centrifuged, washed, and placed in an oven at 40-60 ° C. to dry to obtain Fe-HMMSNs.

[0012] Preferably, step S3 specifically comprises: dissolving 8-10 mg Fe-HMMSNs in 1-2 mL water, and then dissolving 3-4 mg TA and 1-2 mg FeCl3·6H2O in 1-2 mL water respectively. First, the TA solution is mixed with the Fe-HMMSNs solution and stirred for 30-50 min, then the FeCl3·6H2O solution is added and stirred for 20-40 min, and finally the solution is centrifuged and washed with ethanol and water for 2-3 times, and dried in an oven at 40-60°C for 10-12 hours to obtain Fe-HMMSNs@TA-Fe. The volume ratio of TA to FeCl3·6H2O solution is 1:1 to 3:1.

[0013] Another object of the present invention is to provide a method for preparing a molybdenum-based nanozyme having multiple active centers coated with metal polyphenols, referred to as Fe-HMMSNs@TA-Fe.

[0014] The last object of the present invention is to provide applications in terms of enzyme catalytic performance and photothermal performance of metal polyphenol-coated molybdenum-based nanozymes with multiple active centers.

[0015] The beneficial effects of the present invention are:

[0016] The present invention provides a method for preparing a metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers and its application, using MSNs as a carrier, molybdenum acetylacetonate as a molybdenum source, and ferric chloride as an iron source, stirring for 20 hours and then gradient calcining for 4 hours to synthesize nanozymes co-doped with iron and molybdenum MSNs. Subsequently, a metal-acid treatment strategy is adopted to hydrogenate it, and a molybdenum-based nanozyme with multiple types of enzyme catalytic activity (catenases, oxidases, peroxidases) and efficient near-infrared second region (1064nm) photothermal conversion ability will be obtained, and tannic acid (TA) and ferric chloride solution are continued to stir for 30 minutes, and the TA-Fe metal polyphenol network is coated on its surface, which effectively improves the cyclic stability and intratumor-specific catalysis of the molybdenum-based nanozyme. The above-mentioned several-step strategy can develop a molybdenum-based nanozyme with biosafety and cyclic stability and can simultaneously achieve excellent phototherapy performance and chemokinetic therapy performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a transmission electron microscope image of the mesoporous silica provided in Example 1;

[0018] Figure 2 is a transmission electron microscope image of the Fe-MMSNs prepared in Example 1;

[0019] Figure 3 : is a transmission electron microscope image of the Fe-HMMSNs prepared in Example 1;

[0020] Figure 4 This is a transmission electron microscope image of Fe-HMMSNs@TA-Fe prepared in Example 1;

[0021] Figure 5 Zeta potential images of Fe-HMMSNs@TA-Fe prepared in Example 1 before and after coating;

[0022] Figure 6 The photothermal properties of Fe-HMMSNs@TA-Fe prepared in Example 1. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Example 1

[0025] This embodiment provides a metal polyphenol network-coated platinum-based nanozyme with multiple active centers, and the preparation method comprises the following steps:

[0026] (1) Preparation of mesoporous silica (MSNs):

[0027] 0.96 g CTA·Tos, 0.105 g tri(2-hydroxyethyl)amine and 10 mg 1-butyl-3-methyl-imidazolium trifluoromethanesulfonate were dissolved in 50 mL distilled water, stirred at 80°C for 1 h, and then 7.8 mL ethyl orthosilicate was added and stirred for 2 h. The product was then centrifuged at 8000 rpm for 5 min, washed twice with anhydrous ethanol and water in sequence, and dispersed in 150 mL anhydrous ethanol for 24 h in order to remove the template CTA·Tos. After centrifugation at 10000 rpm for 10 min, it was washed twice with anhydrous ethanol and dried. The obtained solid was MSNs.

[0028] The morphology of the prepared MSNs was observed using a transmission electron microscope. Figure 1 As shown in the figure, it can be seen that the MSNs have an obvious dendritic structure inside and the particle size distribution is uniform.

[0029] (2) Preparation of iron-molybdenum oxide co-doped nanozymes (Fe-MMSNs): 30 mg of MSNs were dissolved in anhydrous ethanol, and then a mixed solution containing 2.7 mg of urea and 0.54 g of NH4Cl (solvent: 5 mL of distilled water and 5 mL of anhydrous ethanol) was added. After stirring for 3 h, 0.4893 g of acetylacetonate molybdenum oxide dispersed in 20 mL of anhydrous ethanol was added thereto, and stirring was continued for 8 h. Then 67.6 mg of FeCl3·6H2O dissolved in 3.5 mL of anhydrous ethanol was added and stirred for 24 h. The obtained product was dried in an oven at 60 ° C, the obtained solid was fully ground in a mortar, and finally gradient calcined in a muffle furnace, with the highest temperature at 400 ° C and the calcination time for 6 h to obtain Fe-MMSNs.

[0030] The morphology of Fe-MMSNs was characterized by transmission electron microscopy, and the transmission electron microscopy images were obtained as shown in Figure 2 As shown in the figure, it can be seen that Fe-MMSNs are uniformly dispersed spherical structures with a particle size of about 110 nm.

[0031] (3) Preparation of hydrogenated iron molybdenum oxide loaded in MSNs (Fe-HMMSNs): 100 mg of Fe-MMSNs was dissolved in 20 mL of dilute hydrochloric acid with a concentration of 4 M. Then, 0.15 g of zinc powder was added under rapid stirring at 600 rpm for 3 min to obtain a blue-black product. The product was centrifuged at 10,000 rpm for 5 min, washed with distilled water and anhydrous ethanol, and then dried in an oven at 60°C to obtain Fe-HMMSNs.

[0032] The morphology of Fe-HMMSNs was characterized by transmission electron microscopy, and the transmission electron microscopy images were obtained as follows: Figure 3 As shown in the figure, it can be seen that Fe-HMMSNs have a spherical structure, uniform particle size, obvious mesoporous structure, and a particle size of about 110 nm.

[0033] (4) Coating of metal polyphenol network TA-Fe: 10 mg Fe-HMMSNs was dissolved in 1 mL water, and then 3.2 mg TA and 1.6 mg FeCl3·6H2O were dissolved in 1 mL water respectively. 1 mL TA solution was mixed with 1 mL Fe-HMMSNs solution and stirred for 40 min, then 0.5 mL FeCl3·6H2O solution was added and stirred for 30 min. Finally, the product was centrifuged at 11000 rpm, washed with ethanol and water for 3 times, and dried in an oven at 60°C for 12 h to obtain Fe-HMMSNs@TA-Fe. The volume ratio of TA to FeCl3·6H2O solution was 2:1.

[0034] The prepared Fe-HMMSNs@TA-Fe was tested by transmission electron microscopy. The transmission electron microscopy images are shown in Figure 4 As shown in the figure, it can be seen that compared with the morphology of Fe-HMMSNs, the spherical surface is smoother, the size is increased by about 10nm, and the particle size is about 120nm.

[0035] Figure 5 The Zeta potential picture was used to test the electronegativity of the material surface. It was found that the surface electronegativity of Fe-HMMSNs was positive, the surface electronegativity of TA was negative, and the surface electronegativity of the coated material Fe-HMMSNs@TA-Fe was negative, which proved the successful coating of TA-Fe from the perspective of the electrical properties of the surface charge.

[0036] Figure 6 The photothermal performance of Fe-HMMSNs@TA-Fe is shown in the curve. -2 It has a strong photothermal conversion ability (41.7%) under 1064nm laser irradiation.

[0037] Example 2

[0038] This embodiment provides a metal polyphenol network-coated platinum-based nanozyme with multiple active centers, and the preparation method comprises the following steps:

[0039] (1) Preparation of mesoporous silica (MSNs):

[0040] 0.90 g CTA·Tos, 0.095 g tri(2-hydroxyethyl)amine and 12 mg 1-butyl-3-methyl-imidazolium trifluoromethanesulfonate were dissolved in 60 mL distilled water, stirred at 70 °C for 1.5 h, 8 mL ethyl orthosilicate was added, and stirring was continued for 2.5 h. The product was then centrifuged at 8000 rpm for 5 min, washed twice with anhydrous ethanol and water in sequence, and dispersed in 160 mL anhydrous ethanol for 20 h in order to remove the template CTA·Tos. After centrifugation at 11000 rpm for 8 min, it was washed twice with anhydrous ethanol and dried. The obtained solid was MSNs.

[0041] (2) Preparation of iron-molybdenum oxide co-doped nanozymes (Fe-MMSNs): 28 mg of MSNs were dissolved in anhydrous ethanol, and then a mixed solution containing 3 mg of urea and 0.6 g of NH4Cl (the solvent was 6 mL of distilled water and 6 mL of anhydrous ethanol) was added. After stirring for 3.5 h, 0.52 g of acetylacetonate molybdenum oxide dispersed in 25 mL of anhydrous ethanol was added thereto, and stirring was continued for 7 h. Then 60.5 mg of FeCl3·6H2O dissolved in 3 mL of anhydrous ethanol was added and stirred for 22 h. The obtained product was dried in an oven at 60 ° C, the obtained solid was fully ground in a mortar, and finally gradient calcined in a muffle furnace with a maximum temperature of 400 ° C and a calcination time of 5 h to obtain Fe-MMSNs.

[0042] (3) Preparation of hydrogenated iron molybdenum oxide loaded in MSNs (Fe-HMMSNs): 80 mg of Fe-MMSNs was dissolved in 18 mL of dilute hydrochloric acid with a concentration of 4 M. Then, 0.14 g of zinc powder was added under rapid stirring at 600 rpm and reacted for 4 min to obtain a blue-black product. The product was centrifuged at 10,000 rpm for 5 min, washed with distilled water and anhydrous ethanol, and then dried in an oven at 60°C to obtain Fe-HMMSNs.

[0043] (4) Coating of metal polyphenol network TA-Fe: 15 mg Fe-HMMSNs was dissolved in 1.5 mL water, and then 3 mg TA and 1.5 mg FeCl3·6H2O were dissolved in 1 mL water respectively. 1 mL TA solution was mixed with 1 mL Fe-HMMSNs solution and stirred for 35 min, then 0.5 mL FeCl3·6H2O solution was added and stirred for 25 min. Finally, the product was centrifuged at 11000 rpm for 5 min, washed with ethanol and water for 3 times, and dried in an oven at 60 °C for 10 h to obtain Fe-HMMSNs@TA-Fe. The volume ratio of TA to FeCl3·6H2O solution was 2:1.

[0044] Example 3

[0045] This embodiment provides a metal polyphenol network-coated platinum-based nanozyme with multiple active centers, and the preparation method comprises the following steps:

[0046] (1) Preparation of mesoporous silica (MSNs):

[0047] 0.94 g CTA·Tos, 0.1 g tri(2-hydroxyethyl)amine and 11 mg 1-butyl-3-methyl-imidazolium trifluoromethanesulfonate were dissolved in 65 mL distilled water, stirred at 75 °C for 2 h, and then 7 mL ethyl orthosilicate was added and stirred for 1 h. The product was then centrifuged at 8000 rpm for 5 min, washed twice with anhydrous ethanol and water in sequence, and dispersed in 140 mL anhydrous ethanol for 22 h in order to remove the template CTA·Tos. After centrifugation at 11000 rpm for 8 min, it was washed twice with anhydrous ethanol and dried. The obtained solid was MSNs.

[0048] (2) Preparation of iron-molybdenum oxide co-doped nanozymes (Fe-MMSNs): 35 mg of MSNs were dissolved in anhydrous ethanol, and then a mixed solution containing 2.5 mg of urea and 0.57 g of NH4Cl (the solvent was 10 mL of distilled water and 10 mL of anhydrous ethanol) was added. After stirring for 2.5 h, 0.4785 g of acetylacetonate molybdenum oxide dispersed in 18 mL of anhydrous ethanol was added thereto, and stirring was continued for 8.5 h. Then, 70 mg of FeCl3·6H2O dissolved in 5 mL of anhydrous ethanol was added and stirred for 20 h. The obtained product was dried in an oven at 60 ° C, the obtained solid was fully ground in a mortar, and finally gradient calcined in a muffle furnace with a maximum temperature of 400 ° C and a calcination time of 7 h to obtain Fe-MMSNs.

[0049] (3) Preparation of hydrogenated iron molybdenum oxide loaded in MSNs (Fe-HMMSNs): 90 mg of Fe-MMSNs was dissolved in 19 mL of dilute hydrochloric acid with a concentration of 4 M. Then, 0.16 g of zinc powder was added under rapid stirring at 600 rpm and reacted for 3.5 min to obtain a blue-black product. The product was centrifuged at 10,000 rpm for 5 min, washed with distilled water and anhydrous ethanol, and then dried in an oven at 60°C to obtain Fe-HMMSNs.

[0050] (4) Coating of metal polyphenol network TA-Fe: 20 mg Fe-HMMSNs was dissolved in 2 mL water, and then 4 mg TA and 2 mg FeCl3·6H2O were dissolved in 1 mL water respectively. 1 mL TA solution was mixed with 1 mL Fe-HMMSNs solution and stirred for 45 min, then 0.5 mL FeCl3·6H2O solution was added and stirred for 40 min. Finally, the product was centrifuged at 11000 rpm for 5 min, washed with ethanol and water for 3 times, and dried in an oven at 60 °C for 10 h to obtain Fe-HMMSNs@TA-Fe. The volume ratio of TA to FeCl3·6H2O solution was 2:1.

[0051] By adopting the above technical solution disclosed in the present invention, the following beneficial effects are obtained:

[0052] The present invention discloses a metal polyphenol network-encapsulated mesoporous silica nanozyme doped with ferric hydride molybdenum oxide, which has dual metal catalytic sites, multiple enzyme catalytic activities, good cyclic stability and efficient near-infrared second region (1064nm) photothermal conversion capability, a preparation method and its application. First, the synthesis process is simple and easy, and can be prepared on a large scale. The raw materials are cheap, and the generated nanozymes have uniform particle size distribution and good dispersibility. Second, the prepared nanozyme has catalase-like activity, which decomposes endogenous H2O2 in tumor cells to produce O2, effectively improving hypoxia in the tumor. Subsequently, it exhibits oxidase-like activity, reducing O2 to superoxide anions (·O2 - ), triggering apoptosis of tumor cells. In addition, the excellent peroxidase-like activity exhibited by catalyzing H2O2 to produce ·OH further increases the level of ROS to induce cell apoptosis; thirdly, the nanozyme has efficient near-infrared second region (1064nm) photothermal conversion capability, which can achieve photothermal enhanced tumor catalytic therapy; fourthly, the nanozyme can enhance the cyclic stability under normal physiological conditions to ensure higher material utilization. In summary, the nanozyme has considerable market prospects.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the scope of protection of the present invention.

Claims

1. A method for preparing a metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers, characterized in that: The following steps are involved: S1, preparing mesoporous silica (MSNs) loaded with iron-molybdenum oxide: dissolving MSNs in anhydrous ethanol, adding urea and NH4Cl solution, rapidly stirring for a period of time, adding acetylacetonate molybdenum oxide solution and FeCl3·6H2O solution and stirring again, finally drying in an oven to obtain a solid product, and calcining in a muffle furnace to obtain MSNs loaded with iron-molybdenum oxide, recorded as Fe-MMSNs; S2, preparation of hydrogenated iron molybdenum oxide loaded in MSNs: Fe-MMSNs are uniformly dispersed in dilute hydrochloric acid, and zinc powder is added under rapid stirring conditions. After a period of reaction, a blue-black product is obtained, which is centrifuged, washed several times, and dried in an oven to obtain hydrogenated iron molybdenum oxide loaded on MSNs, which is recorded as Fe-HMMSNs; S3, the metal-polyphenol coordination strategy was used to coat it: Fe-HMMSNs, tannic acid (TA) and FeCl3·6H2O were dissolved in water to form a uniform solution, the TA solution was mixed with the Fe-HMMSNs solution and stirred for 30 to 50 minutes, and then the FeCl3·6H2O solution was added and continued to stir for 20 to 40 minutes. After centrifugation, washing and drying, the TA-Fe metal polyphenol network-coated MSNs loaded with metal-like hydride iron molybdenum oxide was obtained, which was recorded as Fe-HMMSNs@TA-Fe.

2. The method for preparing the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers according to claim 1, characterized in that: The MSNs described in step S1 are prepared by first dissolving 0.8-1.2 g CTA·Tos, 0.1-0.2 g tri(2-hydroxyethyl)amine and 10-15 mg 1-butyl-3-methyl-imidazolium trifluoromethanesulfonate in distilled water, stirring at 80-120° C. for 1-3 h, adding 7-11 mL ethyl orthosilicate, and continuing to stir for 1-3 h. The product is then centrifuged and washed, and the product is dispersed in anhydrous ethanol for 20-26 h in order to remove the template CTA·Tos. After centrifugation, it is washed and dried to obtain the solid MSNs.

3. The method for preparing the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers according to claim 1, characterized in that: Step S1 specifically comprises: dissolving 25-45 mg of MSNs in anhydrous ethanol, then adding a mixed solution of urea and NH4Cl, stirring for 2-3 hours, and then adding 0.4-0.5 g of molybdenum acetylacetonate oxide dispersed in 20-40 mL of anhydrous ethanol, Continue stirring for 5 to 8 hours, then add 60 to 70 mg of FeCl3·6H2O dissolved in 2 to 5 mL of anhydrous ethanol, and stir thoroughly for 20 to 24 hours. The obtained product is dried in an oven at 40 to 60°C, the obtained solid is fully ground in a mortar, and finally calcined in a muffle furnace at a maximum temperature of 400 to 500°C and a calcination time of 4 to 6 hours to obtain Fe-MMSNs.

4. The method for preparing the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers according to claim 2, characterized in that The solvent of the mixed solution of urea and NH4Cl added is 5-10 mL of water and 5-10 mL of anhydrous ethanol.

5. The method for preparing the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers according to claim 1, characterized in that: Step S2 specifically comprises: dissolving 0.1-0.15 g of Fe-MMSNs in 20-40 mL of dilute hydrochloric acid with a concentration of 3-6 M, then adding 0.1-0.2 g of zinc powder under rapid stirring conditions to react for 3-8 min to obtain a blue-black product, which is then centrifuged, washed, and placed in an oven at 40-60 ° C for drying to obtain Fe-HMMSNs.

6. The method for preparing the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers according to claim 1, characterized in that: Step S3 specifically includes: dissolving 8-10 mg Fe-HMMSNs in 1-2 mL water, and then dissolving 3-4 mg TA and 1-2 mg FeCl3·6H2O in 1-2 mL water, respectively. Mixing the TA solution with the Fe-HMMSNs solution, stirring for 30-50 min, adding the FeCl3·6H2O solution thereto, and continuing to stir for 20-40 min, finally centrifuging the product, washing it with ethanol and water for 2-3 times, and drying it in an oven at 40-60° C. for 10-12 h to obtain Fe-HMMSNs@TA-Fe, wherein the volume ratio of TA to the FeCl3·6H2O solution is 1-3.

7. A metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers prepared by the preparation method described in any one of claims 1 to 6.

8. Use of the metal polyphenol network-coated molybdenum-based nanozyme with multiple active centers as described in claim 7 in targeted tumor catalytic therapy.